Poluentes ambientais e sua associação com o desenvolvimento do autismo - Bigolin, Raquel Bringmann (2020)
Autistic Spectrum Disorder (ASD) is recognized for a number of peculiar characteristics related to child behavior and development. These characteristics are associated with the child's neurological development from before birth to the first years of life. Among the main ones are: communication difficulties, problems with language and social interaction, in addition to learning difficulties. Environmental pollution and the reduction of green areas is a reality worldwide, as is the increase in the number of diagnoses of autism cases. In the last decade, there has been an increasing attempt to provide answers about the environmental causes involved in ASD, since since the past decade, the possible factors involved in this etiopathogenesis have been studied. Particularly in the case of Brazil, it is noted that information on the number of individuals who have ASD is still scarce, as well as studies and dissemination on the subject are lacking. In this study we analyze recent work that proposes to study environmental factors possibly involved in the development of ASD. We gathered this information in the form of an integrative literature review article, which constitutes the chapter of this dissertation. The search criteria were articles in the Scielo and Science Direct databases, published in the last 7 years, using the keywords: "autism" and "pesticide" and "environmental pollutants" and "demography" and "autism in brazil". The analyzed studies suggest a strong association between different air pollutants, such as particulate matter (PM), heavy metals and pesticides, and TEA. More studies are still needed to confirm these findings, but we already have indications that it is of great importance to pay attention to the environmental factors involved in the etiopathogenesis of ASD.